The impact of recycling campaign toward community / Shahaida Sapingi - Sapingi, Shahaida (2015)
The purpose of doing this research is to determine how impact the recycle campaign will change the behavior community. This research will be focus on attitude of consumer towards recycle campaign. Consumer Behavior is about people, how they use to select, secure, and dispose of products, services, experiences, or ideas to satisfy needs. It studies characteristics of individual consumers such as demographics and behavioral variables in an attempt to understand people's wants. It also tries to assess influences on the consumer from groups such as family, friends, reference groups, and society in general. Advertisements have great influence in any decision of customers for particular brands or campaign. It is an accepted fact that advertisements can give special attributes upon a product or service that it may have lacked otherwise. The research study focuses on identifying the influence of advertisements on the consumer behavior and attitude.